Sudden cardiac death among Iranian population: a two decades follow-up of Tehran lipid and glucose study - Hossein Toreyhi (Nature Portfolio, 2021)
Abstract Sudden cardiac death (SCD) is described as death within one hour, if observed, from the onset of symptoms, and within 24 h of being alive and well if not observe. Study population includes 3705 men and 4446 women, aged ≥ 30 years. Multivariable Cox proportional hazard models were used to determine the risk factors associated with SCD. After a median follow-up of 17.9 years, 244 SCD (165 in males) occurred. The age-standardized incidence rate (95% confidence intervals (CI)) of SCD was 2.3 (2.1–2.7) per 1000 person-year. Current smoking [Hazard ratio (HR): 2.43, 95% CI: 1.73–3.42], high waist circumference [1.49: 1.04–2.12], hypertension [1.39: 1.05–1.84], type 2 diabetes mellitus [2.78: 2.09–3.69], pulse rate ≥ 90 beats per/minute [1.72: 1.22–2.42] and prevalent cardiovascular disease [1.75: 1.26–2.45] were significant risk factors. The corresponding population attributed fractions (PAF) were 14.30, 16.58, 14.03, 19.60, 7.62, and 8.30, respectively. Being overweight [0.58: 0.40–0.83] and obese [0.61: 0.38–0.98] decreased the risk of SCD. After excluding known diabetes cases from our data analysis, the newly diagnosed diabetes still showed an HR of 2.0 (1.32–3.00) with a PAF of 7.15% in the full adjustment model. To deal with sudden death as a catastrophic outcome, multi-component strategies by policy health makers are suggested.